On Teaching History Of Architecture In Higher Education Or How To Use Sir Banister Fletcher’s A History Of Architecture For A 21st Century Course In Architectural History – An Overview - Julean, Dan-Ionuţ (European Scientific Journal, ESJ, 2016)
Teaching history of architecture to young students may be the most challenging duty for a member of the teaching staff within an educational institution that prepares future architects, in (for) the 21st century. An explanation would be the fact that History of Architecture, as a compulsory subject of the educational curriculum is often regarded as being obsolete and useless. Nowadays generations regard the present as the only conditioning matter for future. Therefore, with few exceptions, the history of architecture is completely forgotten, despite the fact that the theory of architecture sets certain turning points or counterpoints, related to the past – e.g. genius loci (Norberg-Schulz, 1979). Usually the design studios, where they “knead” and collate lines, textures, colours, materials, and images, attract students a lot. They work with space and they create space. But what happens beyond the drawings? What is behind rules and regulations, building-types and facilities, walls and windows? Architecture is where people dwell… (Heidegger, 1975, pp. 221-229). On the other side of the present and future of architecture, lay centuries of history of architecture that usually remain unrevealed – covered in oblivion or totally neglected. That is why, the role of innovation and originality is highly recommended when teaching history, the history of architecture in particular. Thus, this paper focuses on new approaches in architectural higher education, as the result of the courses and seminar classes implemented by the author at the Faculty of Architecture and Urban Planning of Cluj-Napoca.